Performance analysis and optimisation of new strategies for the setup of a multihead weighing process (2020)
This paper highlights the benefits of multihead weighing, a packaging process based on the sum of weights of several individual hoppers wherein total weight of the packed product must be close to a specified target weight while complying with applicable regulations. The paper details into performance analysis and optimisation of new strategies for setting-up the process to achieve an optimal configuration of the machine. Three strategies, designed to optimise the packaging process, are analysed and compared in terms of supplying products to the hoppers. A factorial design of the experimental model is exploited to predict the measures of performance as a function of a variety of control settings. Results of the numerical experiments are used to analyse the sources of variability and to identify the optimum operating conditions for the multihead weigher. Therefore, the findings of this paper will benefit both manufacturer and users of the multihead weigher machine.